Physiological response of nondescript goats drinking water contaminated by tailings dust in subtropical regions - Serakalala, Ntshete William (My University, 2024)
Goat health and reproductive performance in poor, resource-limited communities in mining areas remain increasingly challenged by tailing dust contamination of surface water bodies. The broad objective of the study was to evaluate the effect of tailing dust contamination on surface water bodies on health status of goats. A total of 200 questionnaires were administered to resource-limited households in two villages of Ba-Phalaborwa Local Municipality to assess beliefs and attitudes of resource-limited farmers on the health status of goats drinking water polluted by tailing dusts in contaminated and uncontaminated areas. As a follow-up, the physiological response of 100 goats (n=100) from contaminated and uncontaminated areas were assessed twice during the cool-dry season. Body condition score (BCS), body weight (BWT), FAMACHA score, and corneal opacity (ES) were determined for dry non-lactating does (n=100). The area of the cornea that was extremely opaque was assessed to determine the degree of corneal opacity. Contamination of surface drinking water by tailing dust was ranked highest during the cool-dry season. Urine colour, oedema of the eyelids and high kid mortality rates were perceived as the health indicators for goats drinking water contaminated by tailing dust. Contaminated areas were correlated (P ≤ 0.05) with BCS, BWT, and ES in goats. Goats reared in contaminated areas had lower BCS and BWT (P < 0.001) than goats reared in uncontaminated areas. Goats in contaminated areas had higher ES and FAMACHA scores (P < 0.001) than those in uncontaminated areas. Body condition score (BCS) had a positive (P < 0.001) correlated relationship with ES. Physiological responses of does drinking water contaminated by tailing dust include lower BCS and BWT, in addition to higher ES and FAMACHA scores. It was concluded that the integration of BCS and ES are physiological response of does to consuming water contaminated by tailing dusts in subtropical regions. The integration of BCS and ES should be taken into consideration in goat programme strategies for assessing the health status of goats consuming water contaminated by tailing dust
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2024
Keywords: Tailing dusts; River systems; Water quality; Seasonality; Goat health; Does; Corneal opacity; Subtropical regions; Water quality; Goats; Water -- Pollution; Goat farming; Water-supply, Agricultural -- Quality